2017
DOI: 10.1007/s13593-017-0483-1
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable use of termite activity in agro-ecosystems with reference to earthworms. A review

Abstract: Sustainable agriculture and agro-ecology justify the need to study and understand the role played by ecological processes, and soil biodiversity in particular, in agro-ecosystem functioning. A large number of studies have focused on earthworms in temperate and humid tropical ecosystems and have demonstrated their importance for improving soil biological, physical, and chemical properties in agro-ecosystems. Their "success" is so essential that earthworms are widely considered key species and relevant indicator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 104 publications
(143 reference statements)
0
26
0
3
Order By: Relevance
“…L'effet combiné des facteurs sol et stress hydrique ont entraîné une fragilisation de l'état des plantes en les rendant vulnérables aux termites en saison sèche (Jouquet et al, 2018). Très peu d'espèces de termites s'attaquent aux cultures en bonne santé (Louppe et Zaremski, 2016).…”
Section: Effet De L'attaque De Termites Sur Les Bfaunclassified
See 1 more Smart Citation
“…L'effet combiné des facteurs sol et stress hydrique ont entraîné une fragilisation de l'état des plantes en les rendant vulnérables aux termites en saison sèche (Jouquet et al, 2018). Très peu d'espèces de termites s'attaquent aux cultures en bonne santé (Louppe et Zaremski, 2016).…”
Section: Effet De L'attaque De Termites Sur Les Bfaunclassified
“…Selon la méthode dite « alimentaire », décrite par Han et Ndiaye (1996), qui consiste à fournir aux termites du bois mort pour les détourner des plantes cultivées, le paillis aurait pu jouer un rôle de leurre. D'autres méthodes biologiques et mécaniques de lutte existent comme l'utilisation de champignons entomopathogènes, la stimulation des prédateurs naturels tels que les fourmis (Jouquet et al, 2018), l'application d'extraits d'Azadirachta indica (Tahiri et al, 2011), la destruction des nids.…”
Section: Effet De L'attaque De Termites Sur Les Bfaunclassified
“…Termite activity can also affect crop quality. The scarification of crop tubers by termites can reduce their market value and increase the toxin content in groundnuts (Jouquet et al 2018). Not all termites are pests.…”
Section: Termites As Agricultural Pestsmentioning
confidence: 99%
“…Termite activity was probably an additional contributor to the gap between the fungus-comb chamber and soil environment. Several studies have shown significant enhancement of microbial biomass by termites, while others have found the opposite effect (Adair et al 2008;Jouquet et al 2018). This implies that termites stimulate the relatively inactive microbial communities and accelerate soil N recycling (Frouz 2018).…”
Section: Predicted Nitrogen Stockmentioning
confidence: 99%